Technology and Institutions: What Can Research on Information Technology and Research on Organizations Learn from Each Other?1 - Orlikowski, Wanda J.; Barley, Stephen R. (MIS Quarterly, 2001)
We argue that because of important epistemological differences between the fields of information technology and organization studies, much can be gained from greater interaction between them. In particular, we argue that information technology research can benefit from incorporating institutional analysis from organization studies, while organization studies can benefit even more by following the lead of information technology research in taking the material properties of technologies into account. We further suggest that the transformations currently occurring in the nature of work and organizing cannot be understood without considering both the technological changes and the institutional contexts that are reshaping economic and organizational activity. Thus, greater interaction between the fields of information technology and organization studies should be viewed as more than a matter of enrichment. In the intellectual engagement of these two fields lies the potential for an important fusion of perspectives, a fusion more carefully attuned to explaining the nature and consequences of the techno-social phenomena that increasingly pervade our lives.